The rise and fall of Napoleon Bonaparte - Asprey, Robert B. (Abacus, an imprint of Little, Brown and Company, 2001)
Since his untimely death aged fifty-one in 1821, Napoleon Bonaparte has been often the victim of biographical revisionism that treats him either as a demi-god or as devil incarnate. In the first of this new two-volume biography, Robert Asprey has preferred to treat him as a human being. The Rise and Fall of Napoleon (Volume 1: The Rise) chronicles the beginning of this most extraordinary of lives, from Napoleon's birth in 1769 to the historic Battle of Austerlitz in 1805, when he brilliantly defeated Austro-Russian armies. What emerges is both a fascinating and contradictory figure: a child of the French Revolution who grew to be its master; who exploited national will for what he believed to be national good; who converted surging passions of thirty million persons into an irresistible force to challenge and often topple archaic thrones; whose desire for European reforms ultimately fell victim to feudal superstition and misery. Robert Asprey tells this tale with the even-handedness such a major historical figure deserves. He presents Napoleon as he was - a man dedicated to his vision of himself and his empire--Publisher's description.